Training on Digital Marketing and Redesign of Ecoenzyme Product Packaging Enhances the Productivity of ‘Sri Tanjung SMEs’ - Maulida, Faishal Hilmy; Kusuma, Yudhistya Ayu; Shanti, Mardhatillah (SEEIJ (Social Economics and Ecology International Journal), 2023)
Sri Tanjung is one of the Small & Medium-Sized Enterprises (SMEs) operating in a green economy in Sukosari Village, Kasembon District, Malang Regency. The SMEs make a variety of eco-enzyme-based soaps. This community service aims to address the production and marketing-related issues that Sri Tanjung SMEs deal with. Observation and training tailored to the requirements of Sri Tanjung SMEs constitute the method adopted. Among the conclusions reached are the necessity to enhance manufacturing capacity, which is still constrained by a shortage of human resources; the fact that sales of soap only satisfy local demands using traditional techniques; and the fact that human resources still lack marketing technology skills. Conclusions and suggestions that can be made include training on the usage of Google Business and Google Ads, as well as training on the production and marketing aspects of digital marketing through social media (marketing aspect).